Forgone care and financial burden due to out-of-pocket payments within the German health care system - Patrick Bremer (Health Economics Review, 2014)
Background: The amount of out-of-pocket (OOP) payments within the German health care system has risen steadily within the last years. OOP payments aim to strengthen patients' cost awareness and try to restrict the demand on medical necessary treatments. However, besides the intended decline of non-induced health care services there's a risk that people also forgo necessary treatments because the utilization of health care services depends not only on need-factors but also on the ability to pay for it. Therefore, this paper aims to analyze the determinants of the total amount of OOP payments, the financial burden caused by OOP payments and the relinquishment of health care services due to OOP payments. Data and methods: The empirical analysis is based on cross-sectional data of the German subsample (n = 2851) of the Survey of Health, Ageing and Retirement in Europe (SHARE). SHARE is a representative panel study among private households with persons above the age of 50 years and covers a wide range of topics, e.g. health behavior, health status and information about the socio-economic status. The analysis of the independent variables "total amount of OOP payments", "financial burden due to OOP payments" and "forgone care" is carried out by the means of descriptive as well as multivariate regression methods. Results: Individuals with low income as well as people suffering from chronic illnesses face a higher financial burden and forgo health care services more frequently at the same time. E.g. the financial burden of people who belong to the lowest income quintile is about eight times higher compared to individuals who belong to the highest quintile. The probability of forgone care for this group is about 5.6 percentage points higher [95% CI: 5.2 - 6.0]. Conclusion: Especially for the group of people with chronic illnesses and low-income earners it cannot be ruled out that they also forgo necessary medical treatments due to the relatively high financial burden they face. Hence, it is required to facilitate the access to necessary care for these groups.
Keywords: 330; Out-of-pocket payments; Equity; Forgone care; Sample-selection model; Germany